RANCANG BANGUN APLIKASI BIMBINGAN DAN KONSELING PADA SISWA KELAS XII SLTA (STUDI KASUS : SMAN 1 TAMAN) - Akbar, Jamrodzi Firdhani; Hariadi, Bambang; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
The purpose of this research was to develop an application of guidance and counseling form twelfth grade senior high scholl students. The method that use in this research is SDLC (System Development Life Cycle) Waterfall mode that have 5 steps that is requirement, design, implementation, testing, and maintenance. The result of this research is an application of guidance and counseling that can handle the process of career determination and career guidance for twelfth grade and also can give reports from that two process. The conclusion of this research is the application have been create can handle career determination for the twelfth grade student and career guidance. For futher development, suggested made mobile application for android and IOS that allows users to acces application everywhere and everytime.